2012
DOI: 10.1002/ijc.27954
|View full text |Cite
|
Sign up to set email alerts
|

microRNA and inflammatory gene expression as prognostic marker for overall survival in esophageal squamous cell carcinoma

Abstract: MicroRNAs (miRNAs) and inflammatory genes have a role in the initiation and development of esophageal squamous cell carcinoma (ESCC). In our study, we examined the potential of using miRNA and inflammatory gene expression patterns as prognostic classifiers for ESCC. Five miRNAs and 25 inflammatory-related genes were measured by quantitative reverse transcriptase PCR in tumor tissues and adjacent noncancerous tissues from 178 Chinese patients with ESCC. The expression levels of miR-21 (p = 0.027), miR-181b (p =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 67 publications
0
40
0
Order By: Relevance
“…The miR-181 family exhibits cancer-specific expression patterns, and miR-181b is upregulated in various malignant neoplasms, including breast, pancreas, prostate, esophagus and gastric cancer (15,(26)(27)(28)(29). In gastric cancer cell lines, miR-181b significantly increased cell proliferation, migration and invasion (30).…”
Section: Discussionmentioning
confidence: 99%
“…The miR-181 family exhibits cancer-specific expression patterns, and miR-181b is upregulated in various malignant neoplasms, including breast, pancreas, prostate, esophagus and gastric cancer (15,(26)(27)(28)(29). In gastric cancer cell lines, miR-181b significantly increased cell proliferation, migration and invasion (30).…”
Section: Discussionmentioning
confidence: 99%
“…miR-21 is an oncogenic miRNA that has been shown to be produced at increased levels in EC, and overexpression of miR-21 plays important roles in increasing cell proliferation, migration, invasion, and survival (Li et al, 2013;Wang et al, 2013). Previous studies (Mathé et al 2009;Komatsu et al, 2013;Wang et al, 2013;Zhao et al, 2013) have suggested that miR-21 downregulation inhibits cell growth and invasion and induces cells to apoptose through targeting of the FASL, TIMP3, and RECK genes. A study by Hamano et al (2011) also indicated that miR-21 regulates stem cell function, which is involved in the resistance to chemotherapy in EC.…”
Section: Discussionmentioning
confidence: 99%
“…Altered gene expression, which is the result of gene mutation or dramatic changes in gene regulation, is associated with a variety of diseases. MicroRNAs (miRNAs) act as oncogenes or tumor suppressors, mediating multiple gene expression in human cancers (10,11). Previous studies demonstrated that in ESCC, tumor-suppressive miRNAs of miR-145, miR-133a, miR-133b (12) and miR-143 (13) inhibited tumor cell proliferation and invasion.…”
Section: Introductionmentioning
confidence: 99%